Penguatan Literasi Media Sosial Bagi Perkembangan Anak Usia Dini - Putri, Risma Aliviani; Diah, Moneca; Fauziah, Syifa (UNIVERSITAS NGUDI WALUYO, 2021)
Technology is getting more and more developed well such as gadgets, laptops, household electronics, electronic devices to work and so on, for the last few most trending at this time is gadgets. It seems that gadged itself can have such a huge impact on value and culture. Social media literacy must be planted early, because with social media literacy, children will understand what the benefits and impacts of social media and children are farthest from the negative impacts. Implementation of activities held at TK Pelangi Nusantara 05 with the method of providing health education and strengthening about early childhood development and social media divided into 2 stages of implementation. Data collection instruments in the form of questionnaires. The knowledge of parents after being given early childhood development information mostly has good knowledge of 27 people (69.23%) and enough knowledge of 12 people (30.77%). knowledge of parents after being given social media education is mostly knowledgeable 28 (71.8%) (28.2%). This social media literacy strengthening activity becomes a means of communication, education and discussion that is able to provide education and forgiveness for parents in efforts to supervise, mentor and provide solutions for the use of social media that is appropriate and effective for early childhood development.AbstrakTeknologi semakin lama semakin berkembang dengan baik seperti gawai, laptop, alat elektronik rumah tangga, alat elektronik untuk bekerja dan lain sebagainya, untuk beberapa terakhir yang paling trend pada saatini adalah gawai. Sepertinya gadged sendiri dapat memberikan dampak yang begitu besar pada nilai dan kebudayaan.Literasi media sosial harus ditanam sejak dini, karena dengan adanya literasi media sosial, anak akan memahami apa manfaat dan dampak dari media sosial dan anak pun terjauh dari dampak negatifnya. Pelaksanan kegiatan dilaksnakan di TK Pelangi Nusantara 05 dengan metode pelaksanaan pemberian pendidikan kesehatan dan penguatan tentang perkembangan anak usia dini dan media sosial yang terbagi menjadi 2 tahap pelaksanaan. Instrumen pengumpulan data berupa kuesioner. Pengetahuan orang tua sesudah diberikan informasi perkembangan anak usia dini sebagian besar memiliki pengetahuan baik sejumlah 27 orang (69,23%) dan pengetahuan cukup 12 orang (30,77%). pengetahuan orang tua sesudah diberikan edukasi media sosial sebagian besar berpengetahuan baik 28 (71,8%) cukup (28,2%). Kegiatan penguatan literasi media sosial ini menjadi sarana komunikasi, edukasi dan diskusi yang mampu memberikan edukasi dan maafaat bagi orangtua dalam upaya pengawasan, pendampingan dan memberikan solusi penggunaan media sosial yang tepat dan efektif bagi perkembangan anak usia dini.